Toll-like receptor 7 protects against intestinal inflammation and restricts the development of colonic tissue-resident memory CD8+ T cells - Hamade, Hussein; Tsuda, Masato; Oshima, Naoki; Stamps, Dalton T.; Wong, Michelle H.; Stamps, Jasmine T.; Thomas, Lisa S.; Salumbides, Brenda C.; Jin, Caroline; Nunnelee, Jordan S.; Dhall, Deepti; Targan, Stephan R.; et al. (Frontiers in Immunology, 2024)
The maintenance of intestinal homeostasis depends on a complex interaction between the immune system, intestinal epithelial barrier, and microbiota. Alteration in of one of these components could lead to the development of inflammatory bowel diseases (IBD). Variants within the autophagy gene ATG16L1 have been implicated in susceptibility and severity of Crohn’s disease (CD). Individuals carrying the risk ATG16L1 T300A variant have higher caspase 3-dependent degradation of ATG16L1 resulting in impaired autophagy and increased cellular stress. ATG16L1-deficiency induces enhanced IL-1 secretion in dendritic cells in response to bacterial infection. Infection of ATG16L1-deficient mice with a persistent strain of murine norovirus renders these mice highly susceptible to dextran sulfate sodium colitis. Moreover, persistent norovirus infection leads to intestinal virus specific CD8+ T cells responses. Both, Toll-like receptor 7 (TLR7), which recognizes single-stranded RNA viruses, and ATG16L1, which facilitates the delivery of viral nucleic acids to the autolysosome endosome, are required for anti-viral immune responses. However, the role of the enteric virome in IBD is still poorly understood. Here, we investigate the role of TLR7 and ATG16L1 in intestinal homeostasis and inflammation. At steady state, Tlr7-/- mice have a significant increase in large intestinal lamina propria (LP) granzyme B+ tissue-resident memory CD8+ T (TRM) cells compared to WT mice, reminiscent of persistent norovirus infection. Deletion of Atg16l1 in myeloid (Atg16l1ΔLyz2) or dendritic cells (Atg16l1ΔCd11c) leads to a similar increase of LP TRM. Furthermore, Tlr7-/- and Atg16l1ΔCd11c mice were more susceptible to dextran sulfate sodium colitis with an increase in disease activity index, histoscore, and increased secretion of IFN and TNFα. Treatment of Atg16l1ΔCd11c mice with the TLR7 agonist Imiquimod attenuated colonic inflammation in these mice. Our data demonstrate that ATG16L1-deficiency in myeloid and dendritic cells leads to an increase in LP TRM and consequently to increased susceptibility to colitis by impairing the recognition of enteric viruses by TLR7. In conclusion, the convergence of ATG16L1 and TLR7 signaling pathways plays an important role in the immune response to intestinal viruses. Our data suggest that activation of the TLR7 signaling pathway could be an attractive therapeutic target for CD patients with ATG16L1 risk variants.